2012
DOI: 10.1371/journal.pone.0044799
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Decreases Resting State Functional Network Connectivity in Healthy Subjects: Implications for Antidepressant Drug Action

Abstract: Increasing preclinical and clinical evidence underscores the strong and rapid antidepressant properties of the glutamate-modulating NMDA receptor antagonist ketamine. Targeting the glutamatergic system might thus provide a novel molecular strategy for antidepressant treatment. Since glutamate is the most abundant and major excitatory neurotransmitter in the brain, pathophysiological changes in glutamatergic signaling are likely to affect neurobehavioral plasticity, information processing and large-scale change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
168
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 237 publications
(196 citation statements)
references
References 65 publications
19
168
2
1
Order By: Relevance
“…Here, we offer a neurobiological explanation for the known antidepressive action of sleep deprivation. using a seed region identical to a previous work (center of this region: x = −8, y = −49, z = 28) (23). It is important to note that, consistent with previous studies (22,24), sleep deprivation reduced functional connectivity of the PCC with the ACC (BA 32; coordinates: +5, +43, +3; z score = 3.7173, P = 0.000201; cluster size = 359 mm 3 ) (Fig.…”
Section: Significancesupporting
confidence: 83%
See 1 more Smart Citation
“…Here, we offer a neurobiological explanation for the known antidepressive action of sleep deprivation. using a seed region identical to a previous work (center of this region: x = −8, y = −49, z = 28) (23). It is important to note that, consistent with previous studies (22,24), sleep deprivation reduced functional connectivity of the PCC with the ACC (BA 32; coordinates: +5, +43, +3; z score = 3.7173, P = 0.000201; cluster size = 359 mm 3 ) (Fig.…”
Section: Significancesupporting
confidence: 83%
“…The first revealed reduced functional connectivity between DN and hippocampus after 7 d of citalopram administration (35). The second showed reduced DN connectivity with the PCC and the pregenual ACC 24 h after ketamine infusions (23). These studies support the hypothesis that reducing DN connectivity to subcortical structures and the DMN network may represent a biomechanism of antidepressant action.…”
Section: Discussionsupporting
confidence: 56%
“…Antidepressant doses of ketamine decreased the default mode connectivity (Scheidegger et al, 2012) and reduced core symptoms of PTSD, including avoidance (Feder et al, 2014). Based on these observations in humans and our findings in mice, we hypothesize that silent synapses underlie the enhanced functional connectivity in mental disease, whereas positive effects of ketamine result from their elimination.…”
Section: Ketamine Against Psychological Traumasupporting
confidence: 64%
“…Studies of humans revealed enhanced functional connectivity between the anterior cingulate cortex and right amygdala in PTSD (Lanius et al, 2010) and within the default mode network in depression (Scheidegger et al, 2012). Antidepressant doses of ketamine decreased the default mode connectivity (Scheidegger et al, 2012) and reduced core symptoms of PTSD, including avoidance (Feder et al, 2014).…”
Section: Ketamine Against Psychological Traumamentioning
confidence: 99%
“…Although inhibitory GABA has recently been shown to mediate EEG taskevoked measures like gamma band oscillations (Lally et al, 2014;Muthukumaraswamy, Edden, Jones, Swettenham, & Singh, 2009), studies on excitatory glutamate modulation of EEG measures have been reported less widely (for exceptions, see Lally et al, 2014; for animal studies, see MoralesVillagrán, Medina-Ceja, & López-Pérez, 2008). Glutamate is an excitatory transmitter that fMRI and magnetic resonance spectroscopy (MRS) analyses have shown to mediate resting state activity, including both intra-regional activity levels and trans-regional functional levels (Duncan, Enzi, Wiebking, & Northoff, 2011;Duncan et al, 2013;Enzi et al, 2012; also see Falkenberg, Westerhausen, Specht, & Hugdahl, 2012;Scheidegger et al, 2012). Such glutamatergic modulation of the resting state suggests that glutamate might mediate the influence of pre-stimulus state activity on stimulus-related activity.…”
mentioning
confidence: 99%